2022
DOI: 10.1007/s00330-022-09265-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a highly accelerated post-contrast wave-controlled aliasing in parallel imaging (CAIPI) 3D-T1 MPRAGE compared to standard 3D-T1 MPRAGE for detection of intracranial enhancing lesions on 3-T MRI

Abstract: Objectives High-resolution post-contrast T1-weighted imaging is a workhorse sequence in the evaluation of neurological disorders. The T1-MPRAGE sequence has been widely adopted for the visualization of enhancing pathology in the brain. However, this three-dimensional (3D) acquisition is lengthy and prone to motion artifact, which often compromises diagnostic quality. The goal of this study was to compare a highly accelerated wave-controlled aliasing in parallel imaging (CAIPI) post-contrast 3D T1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[5][6][7] Recent advances in medical imaging technology have enabled the development of fast MRI techniques that can reduce acquisition times while still providing high-quality diagnostic images. [8][9][10][11][12][13][14][15][16][17] These fast-imaging techniques can mitigate the impact of artifacts from patient motion, improve patient comfort, reduce anxiety, and optimize workflow thereby allowing for quicker access to imaging results. 18 Accelerated MRI techniques such as parallel imaging and compressed sensing have been developed and applied in recent years, leading to a marked reduction in acquisition times.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Recent advances in medical imaging technology have enabled the development of fast MRI techniques that can reduce acquisition times while still providing high-quality diagnostic images. [8][9][10][11][12][13][14][15][16][17] These fast-imaging techniques can mitigate the impact of artifacts from patient motion, improve patient comfort, reduce anxiety, and optimize workflow thereby allowing for quicker access to imaging results. 18 Accelerated MRI techniques such as parallel imaging and compressed sensing have been developed and applied in recent years, leading to a marked reduction in acquisition times.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, precontrast Wave-CAIPI MPRAGE has been validated in volumetric analysis including patients with dementia using 20-and 32-channel coils [12,13]. Also, recent study demonstrated that fast scan using contrast-enhanced Wave-CAIPI 3D T1-MPRAGE was noninferior to the 3D T1-MPRAGE sequence in visualizing and diagnosing enhancing brain lesions [14].…”
Section: Introductionmentioning
confidence: 99%
“…These flow-related artifacts are well known in MRI and may have anomalous appearances, depending on the k -space sampling pattern. Flow-related artifacts have been observed in contrast-enhanced Wave-CAIPI 3D T1-weighted MPRAGE and have an atypical appearance, manifesting as smearing of T1 hyperintense signal in the brainstem, subcortical nuclei, and other areas of the brain parenchyma [ 11 ]. Such artifacts introduce a diagnostic conundrum for the interpreting radiologist as they can mimic enhancing lesions and may require callback for repeat imaging with conventional non-accelerated MR sequences, posing a critical barrier to wider clinical adoption of this technique.…”
Section: Introductionmentioning
confidence: 99%